The role played by the third sector in fostering youth empowerment in Zimbabwe: the case of Zimbabwe Red Cross Society in Highfields (2010-2013) - Dirwai, Gift (Midlands State University, 2017)
This study is aimed at assessing the role played by third sector in fostering youth empowerment in Zimbabwe and a case study of Zimbabwe Red Cross Society in Highfields was used. The study was targeting youths in Highfields assessing the economic political and social impacts of the organisation to the youth. 40 respondents managed to take part in the research and all filled in questionnaires which were semi-structured with sections A, B and C. A total of 23 males and 17 females took part in the questionnaires and 4 interviews were carried out, 2 to staff and 2 to youth members. The questionnaires and interview questions were structured in a way that they would come up with a clear picture of the whole empowerment schemes. The results were that the empowerment initiatives or schemes have managed to empower the young people economically, politically and also socially. Economically, the scheme has managed to create employment, income generation initiatives, project formulation and management skills, funding of already existing youths programmes and the Youth Fund. Socially, the empowerment schemes also have managed to upgrade livelihoods, nutritional gardens, computing skills and enhancing life skills. Regardless of various challenges faced by youths and the organisation in the empowerment scheme, youth empowerment has been pivotal as a tool for poverty reduction or alleviation and providing an opportunity for young people to up bring their Human Development Index and being key players in attaining sustainable development and empowerment.